SPECIES COMPOSITION OF TRAWLER LANDINGS AT SASSOON DOCK, BOMBAY, DURING 1971 - Pillai, S Krishna (Indian Journal of Fisheries, 2011)
The estimated monthly catch at Sassoon Dock during January to December in 1971 fluctuated between 189.8 to 2076.2 tonnes, with an average of 995.6 tonnes, and formed 49.9%of the total catch. Best catches were during October and November. The Sciaenids and penaeid prawns together contributed 53.83% of the total catch. The Sciaenids dominated the catch from January to July and penaeid prawns, from September to December. In the quarterly catch-composition, sciaenids occupied first place in third and fourth quarters. Penaeid prawns and Sciaenids constituted 31% and 23% of the annual catch followed by Coilia dussumieri 9%, Palaemon temipes 9%, Elasmobranch 6%, Harpodon nehereus 3%, Polynemus spp. 2%, Lactaiiiis lactams 2%, Vpeneus spp. 2% and Nemipterus spp. 2%.